Die Folklore Südosteuropas Eine komparative Übersicht - Puchner, Walter (2016)
This comparative investigation is focused on the comparison of contents, themes, topics, motives, but also symbolism, stereotype situations, patterns of behavior etc. of sung and narrated oral text in South-east Europe. Great importance was given to bibliography, usually difficult to compile in a time-consuming process; a separate part at the end of the volume is dedicated to a bibliographie résonée, arranged according to countries and genres; this will facilitate further and more specific research in special fields of interest. This book offers for the first time a comparative survey of nearly all genres of the traditional oral folklore of Southeast Europe, independent from language, ethnic grouping, national boarders, religion and confessions; in this way the high degree of homogenity of the highly developed traditional oral culture in the historical Balkans is documented as well as the high numbers of variants and versions and the superb literary quality of these orally transmitted lingual manifestations, in some cases equal to the written literature of the region.